Screening of synthesized nanoparticle and antineoplastics cytotoxicity against drug resistant breast cancer cells - Darmadi, Jason (2024)
Breast cancer is regarded as a major global health issue due to its high incidence and mortality rate. They are also becoming harder to treat due to the emergence of multidrug resistance (MDR), rendering anticancer drugs less sensitive than ever. Therapeutic nanoparticles and novel bio-derived drugs can be used as a potential replacement for chemo-drug-resistant breast cancer. This study was performed to investigate the resistance of breast cancer cells against a multitude of drugs, as well as to evaluate whether certain nanoparticles could induce cytotoxicity. Four antineoplastic agents, Cisplatin (CDDP), Paclitaxel (PTX), Alpha-Mangostin (A-MG), and Andrographolide (Andr-G), as well as three nanoparticles, synthesized gold nanoparticles (AuNPs), silver nanoparticles (AgNPs), and graphene oxide (GO), were investigated for cytotoxicity against non-chemo-resistant breast cancer MCF-7, chemo-resistant MCF-7-CR, and MDR MDA-MB-231 cell lines. AuNPs and AgNPs were synthesized via chemical reduction using reducing agents NaBH4 and ascorbic acid, where they were further characterized. Treatment of GO was coupled with UV-B irradiation to determine the influence on cytotoxicity against breast cancer cells. It was found that PTX was the most potent yet easiest to be desensitized among all four drugs, whereas A-MG and Andr-G were less prone to be desensitized in longer duration treatment, with 25 µM of A-MG resulting in about 20% cell viability. Ascorbic acid-reduced AuNPs were found to be spherical with a size of 170 nm, zeta potential of -36 mV, and polydispersity index of about 17%. NaBH4-reduced AgNPs were also characterized to have irregular shapes at around 680 nm in size and a zeta potential of -21 mV. AgNPs and AuNPs were less potent against drug-resistant breast cancer cells. In MCF-7 cells, ascorbic acid-reduced AgNPs and NaBH4-reduced AuNPs caused 50% and 25% cell death using 10 µM, respectively. GO was observed to be toxic to both MCF-7 and MDA-MB-231, with viability observed at 70% on MCF-7 for 100 µg/mL GO. UV-B irradiation influenced cytotoxicity in MCF-7 by increasing potency from 80% to 50% cell viability after 3h of GO incubation and 10 mJ/cm2 exposure. GO was more toxic on MCF-7 and MDA-MB-231 cells, whereas MCF-7-CR was more susceptible to both AgNPs and AuNPs. Further studies on the mechanism of action between nanoparticles, drugs, and cancer cells are necessary. The inclusion of different drug-resistant breast cancer cells as well as normal cells is also necessary to further compound the potential therapeutic importance of the study.